Group Counselling with Systematic Desensitization and Emotional Freedom Techniques to Reduce Public Speaking Anxiety (Jurnal Bimbingan Konseling, 2018)
Public Speaking or the ability to speak in public is one of basic competencies that must be owned by students. However, apparently, there found many students having public speaking anxiety and in high category. Regarding this problem, this study was aimed at examining the effectiveness of a group counselling with desensitization technique and emotional freedom technique in reducing students' public speaking anxiety. The implementation of those techniques were done twice in each group counselling service. Meanwhile, the research method employed was mixed anova repeated measures test design by involving 16 students having high level public anxiety chosen from 100 students by using purposive sampling. Further, the results of mixed anova repeated measure showed thatthe group counselling with systematic desensitization technique and emotional freedom technique (EFT) was proved to be effective in reducing the public speaking anxiety of students. Besides, seen from the average score and time effect, emotional freedom technique resulted higher decrease than systematic desensitization technique. For more, the more emotional freedom technique was given, the higher decrease of the public speaking anxiety of students would result.